THE GOLDEN PASSPORT : Harvard Business School, The Limits of Capitalism, and the Moral Failure of the MBA Elite - McDonald, Duff
With The Firm, financial journalist Duff McDonald pulled back the curtain on consulting giant McKinsey and Company. In The Golden Passport, he reveals the inner works of a singular nexus of power, ambition, and influence: Harvard Business School. Harv